DESIGNING WEBSITES TO PT WAIRAU INDOSTONE USING MACROMEDIA DREAMWEAVER MX 2004 - Donny Fransye Boyoh; Riris Ristyawati,SKom,MMSI (Jurnal Sistem Informasi, 2005)
PT Wairau Indostone is a company engaged in paving block / stone decorative conducting the sale, thus the need for strong efforts in providing optimal information to prospective customers. As a key to the success of this company is the promotion and information services are detailed to be able to show a level of service expected. The purpose of scientific writing is to provide information that sedetil-details to potential customers. In connection with this writing, the framework put forward the theory that writing about Web site design and promotion of the purposes of this research is how companies promote merchandise using the Internet media such as website information. The survey results revealed that the company should pay more attention to the needs of a fast and complete information to distributors located in areas further afield in order to increase productivity is better.